Main directions of prophylaxis of untimely mortality from cardiovascular diseases - A. T. Adamyan; S. Yu. Kladov (Бюллетень сибирской медицины, 2009)
The mortality of Tomsk people aged from 15 to 74 from diseases of the blood circulation system have been studied for 1990—2001 and main risk factors have been determined. For the 12-year period, the mortality increased in all the main classes of causes of death. The analysis of differences in male and female mortality from individual causes of death shows that cardiovascular diseases and violent death in the active working age are major contributors to mortality differentiation depending on sex. Four risk factors can be separated: high arterial tension, high cholesterol level, smoking, and excessive alcohol consumption. They determine 87.5% in total mortality and 58.5% in the years of life with disability. Prophylaxis of mortality from circulatory diseases should be aimed, first of all, at these groups of factors.